Aldolase exists in both the fluid and solid phases of cytoplasm [published erratum appears in J Cell Biol 1988 Dec;107(6 Pt 1):following 2463] (The Rockefeller University Press, 1988)
We have prepared a functional fluorescent analogue of the glycolytic enzyme aldolase (rhodamine [Rh]-aldolase), using the succinimidyl ester of carboxytetramethyl-rhodamine. Fluorescence redistribution after photobleaching measurements of the diffusion coefficient of Rh-aldolase in aqueous solutions gave a value of 4.7 x 10(-7) cm2/S, and no immobile fraction. In the presence of filamentous actin, there was a 4.5-fold reduction in diffusion coefficient, as well as a 36% immobile fraction, demonstrating binding of Rh-aldolase to actin. However, in the presence of a 100-fold molar excess of its substrate, fructose 1,6- diphosphate, both the mobile fraction and diffusion coefficient of Rh- aldolase returned to control levels, indicating competition between substrate binding and actin cross-linking. When Rh-aldolase was microinjected into Swiss 3T3 cells, a relatively uniform intracellular distribution of fluorescence was observed. However, there were significant spatial differences in the in vivo diffusion coefficient and mobile fraction of Rh-aldolase measured with fluorescence redistribution after photobleaching. In the perinuclear region, we measured an apparent cytoplasmic diffusion coefficient of 1.1 x 10(-7) cm2/s with a 23% immobile fraction; while measurements in the cell periphery gave a value of 5.7 x 10(-8) cm2/s, with no immobile fraction. Ratio imaging of Rh-aldolase and FITC-dextran indicated that FITC-dextran was relatively excluded excluded from stress fiber domains. We interpret these data as evidence for the partitioning of aldolase between a soluble fraction in the fluid phase and a fraction associated with the solid phase of cytoplasm. The partitioning of aldolase and other glycolytic enzymes between the fluid and solid phases of cytoplasm could play a fundamental role in the control of glycolysis, the organization of cytoplasm, and cell motility. The concepts and experimental approaches described in this study can be applied to other cellular biochemical processes.